Mate Choice, Sex Roles and Sexual Cognition in Vertebrates: Mate Choice Turns Cognition or Cognition Turns Mate Choice? - Fuss, Theodora (Frontiers in Ecology and Evolution, 2021)
The idea of “smart is sexy,” meaning superior cognition provides competitive benefits in mate choice and, therefore, evolutionary advantages in terms of reproductive fitness, is both exciting and captivating. Cognitively flexible individuals perceive and adapt more dynamically to (unpredictable) environmental changes. The sex roles that females and males adopt within their populations can vary greatly in response to the prevalent mating system. Based on how cognition determines these grossly divergent sex roles, different selection pressures could possibly shape the (progressive) evolution of cognitive abilities, suggesting the potential to induce sexual dimorphisms in superior cognitive abilities. Associations between an individual’s mating success, sexual traits and its cognitive abilities have been found consistently across vertebrate species and taxa, providing evidence that sexual selection may well shape the supporting cognitive prerequisites. Yet, while superior cognitive abilities provide benefits such as higher feeding success, improved antipredator behavior, or more favorable mate choice, they also claim costs such as higher energy levels and metabolic rates, which in turn may reduce fecundity, growth, or immune response. There is compelling evidence in a variety of vertebrate taxa that females appear to prefer skilled problem-solver males, i.e., they prefer those that appear to have better cognitive abilities. Consequently, cognition is also likely to have substantial effects on sexual selection processes. How the choosing sex assesses the cognitive abilities of potential mates has not been explored conclusively yet. Do cognitive skills guide an individual’s mate choice and does learning change an individual’s mate choice decisions? How and to which extent do individuals use their own cognitive skills to assess those of their conspecifics when choosing a mate? How does an individual’s role within a mating system influence the choice of the choosing sex in this context? Drawing on several examples from the vertebrate world, this review aims to elucidate various aspects associated with cognitive sex differences, the different roles of males and females in social and sexual interactions, and the potential influence of cognition on mate choice decisions. Finally, future perspectives aim to identify ways to answer the central question of how the triad of sex, cognition, and mate choice interacts.